AUDIT TATA KELOLA SISTEM INFORMASI PADA PT INTERPARK INDUSTRIES BATAM MENGGUNAKAN KERANGKA KERJA COBIT 4.1 - Pasaribu, Eni Debora; Amrizal, Amrizal (Computer Science and Industrial Engineering, 2021)
Currently, the company has implemented an information system to support the running of the business, both for large and small investments. PT Interpark Industries Batam which is engaged in manufacturing carton boxes and printer ink is one of the many companies in Batam that has used an information system, namely, the HICOM Management System (HMS). In using the system, there is still a problem in the data storage process of incoming and outgoing goods that are not in accordance with the actual, so it takes more time to review. Based on these problems, it is necessary to carry out an audit of system governance that is used to determine which maturity level the system is at. In conducting the audit, the method used is the COBIT 4.1 framework with the sub domains PO2, DS11, AI3. The results showed that the average maturity level of the HMS system is at level 2 - Repeatable but intuitive.